Operation "Enduring Freedom" and the fragmentation of international legal culture : comparing US common law and civil law perspectives on the international use of force - Kredel, Nicolas (Schriften zum Völkerrecht, 2006)
Hauptbeschreibung In legal discourse, culture matters. The current debate an the international use of force experiences a transatlantic divide between the US and Continental Europe. This divide can be explained by the fragmentation of legal culture. Continental-European civil law and US common law culture fundamentally differ with regard to the role of the judicial process, the method of legal reasoning, the general paradigm of legal analysis, the value of neutrality, and the required degree of formalism. In the field of the international use of force, cultural differences shape int.